Inventing mobility for all : mastering mobility-as-a-service with self-driving vehicles - Herrmann, Andreas; Jungwirth, Johann, 1973- (Emerald Publishing Limited, 2022)
Inventing Mobility For All: Mastering Mobility-as-a-Service with Self-Driving Vehicles explores 'Mobility-as-a-Service' and explains the impact of this mobility concept on social and societal life, as well as on global travel behaviours. In this volume, Andreas Herrmann and Johann Jungwirth powerfully illustrate that mobility is a fundamental human right that can best be fulfilled with new autonomous vehicle development and use, showcasing how these forms of mobility will improve accessibility for the disabled, aid protection for the environment and to open how we design our cities in completely new ways.